The confessions of Rabbi Samson de Louhans : an analysis of the anti-talmudic procedure in Chambéry in 1417 - Fidora, Alexander (Henoch, 2024)
One of the most important sources on the Talmud trial in Savoy in the year 1417 is the hitherto unedited treatise De publicatione haeresum contentarum in Talmud by André Dias de Escobar. The Portuguese cleric and eyewitness to the Chambéry proceedings against the Talmud provides a fairly detailed account of the events, including a comprehensive list of confessions attributed to the prominent rabbi Samson de Louhans. This article presents a philological and doctrinal analysis of the rabbi’s alleged confessions, which have come down to us only in André’s work. It argues that these confessions do not reflect the actual circumstances of the Jewish community in Savoy but rather are based on a combination of well-established literary models. Consequently, the document must be considered a prime example of the distinctly intertextual dimension of anti-Rabbinic discourse in the Middle Ages.